The promoting effect of exercise motivation on physical fitness in college students: a mediation effect model - Yudu Liu; Xiaobing Zhai; Yanan Zhang; Can Jiang; Jing Zeng; Mei Yang; Xinyan Xie; Feng Zhou; Bing Xiang (BMC, 2023)
Abstract Background In recent years, the physical fitness situation of college students is worrying in China. Exercise motivation is of great importance for the physical activity and physical fitness. However, existing studies have paid limited attention to the specific effect between exercise motivation, physical activity and physical fitness, and even less to the different genders and exercise motivation dimensions. This study aimed to investigate the promoting effect of sport motivation on physical fitness with different gender and dimension in college students. Methods Physical fitness levels of 2544 college students in Wuhan and Jingzhou city were measured. Exercise motivation and physical activity was assessed using the Chinese version of the motives for physical activities measure-revised scale and the physical activity survey scale, respectively. Correlation analysis and structural equation model were used to explore the relationship between exercise motivation, physical activity and physical fitness. Bootstrap method was used to test the mediating effect. Multilevel regression analysis was used to examine the effects of different dimensions of exercise motivation on PF. Results The exercise motivation of college students was directly related to physical fitness (effect value: 0.307) or indirectly related through the mediating effect of physical activity (effect value: 0.092). The mediation effect percentage of physical activity on exercise motivation and physical fitness in male (51.20%) was greater than female (27.18%), and the standardized regression coefficient of the health dimension to PF was β = 0.151, P < 0.001, and the competence dimension to PF was β = 0.189, P < 0.001. Conclusions The exercise motivation of college students can directly influence PF or indirectly influence PF through the mediating effect of PA. The promoting effect of exercise motivation and PA on PF in college students is related to gender and dimensions of exercise motivation. Therefore, we can improve physical fitness levels of college students by promoting their exercise motivation (especially for health motivation and competence motivation) and increasing their participation in physical activity. This study provides new strategies for improving physical fitness in college students.